Component age estimates for the Hell Gap Paleoindian site and methods for chronological modeling of stratified open sites. Issue 2 (24th July 2017) - Pelton, Spencer R.; Kornfeld, Marcel; Lou Larson, Mary; Minckley, Thomas
Abstract: The Hell Gap National Historic Landmark, located on the northwestern plains of Wyoming, is one of the most important Paleoindian archaeological sites in North America because it contains a stratified sequence of occupations spanning nearly the entirety of the Paleoindian period. Although Hell Gap is central to archaeological knowledge concerning North American Paleoindian chronology, consistently assigning component ages has been problematic due to conflicting radiocarbon determinations from individual strata, stratigraphic age reversals in age-depth relationships, and other issues related to the stratified open campsite. Toward resolving the Hell Gap chronology, we devised a procedure for correcting age-depth relationships for incorporation in chronostratigraphic models and then used the Bayesian age-depth modeling qprocedures in Bchron to estimate the ages of 11 stratified components present at Hell Gap Locality 1. We present these age estimates and discuss their significance to Paleoindian chronology. Notable aspects of our chronology include a revised age estimate for the Goshen complex, the identification of three Folsom components spanning the entirety of the Folsom temporal range, and relatively young age estimates for the Late Paleoindian Frederick/Lusk component(s) at Locality 1. More broadly, our study demonstrates a procedure for creating chronometric models of stratigraphically complicated open stratified sites of any type.